(untitled) (Annals of Medical Research, 2021)
Aim: The aims of this study were to define the dynamic loading pattern of the foot in healthy adolescents and to investigate the differences between boys and girls.Material and Methods: n = 89 adolescents (n = 42 girls, n = 47 males) using right hand-preferred and have normal body mass index (18.5- 24.9 kg/m2) were included in the study. Dynamic foot pressure analysis was used to determine the foot dynamical load patterns of the participants. The results were compared by considering be male or female factor and right-left foot dynamic loadingpattern.Results: In the comparison between the groups, it was seen that the contact percentages and active contact areas of the different regions of the feet were different in boys and girls (p 0.05). When the right-left foot load patterns were compared, it was seen that the load transfer in the right foot progressed to the anterior medial and the left foot showed a delay in the load transfer processes (p 0.05).Conclusion: Boys walked with a wider contact percentage in the left foot and wider metatarsal and heel active contact areas in both feet than in girls. Furthermore, on the preferred side (right) the load transfer is positioned on the anterior medial of the foot, while the main difference in the other foot is due to the delay in reaching the maximum pressure.